New interpretation of the provenance of crystalline material from Oligocene flysch deposits of the Skole Nappe, Poland: evidence from heavy minerals and clasts in the Nowy Borek section - Salata, Dorota; Uchman, Alfred (Geologos, 2019)
The Futoma Member (Oligocene, Rupelian) of the Menilite Formation is present only in the northern part of the Skole Nappe. Some diatomitic layers of this member in the Nowy Borek section contain coarse-grained detrital material composed of a variety of metamorphic, volcanic and sedimentary rock fragments. The material derives from primary and secondary sources. Most abundant are debris of metamorphic rocks, mostly gneisses and mica schists. The metamorphic origin of these rocks is confirmed by the composition of heavy mineral assemblages and garnet chemistry. These rocks could have been transported from a local source located close to the margin of the Skole Basin or within that basin. The volcanic rocks reflect Paleogene volcanic activity that was widespread in the Carpathian region. Cherts, which could have been subjected to synsedimentary erosion, may have been derived from the older portions of the same formation.